Predicting the effects of measures to promote public passengers transport - Lep, Marjan; Hmelak, Simon (Journal for Geography, 2011)
A more sustainable mobility has been strived for in Slovenia in the past years, yet the situation in the field has not shown adequate results. In developing the public transport system experts are trying to find answers to a question about where to invest public money to achieve a shift in the selection of the desired mode of transport. In order to support decision makers, the model was developed in the form of an equation with can predict effects of more authentic measures such as integrated ticketing, significant decrease of fares, change of parking rates in cities, increase of train services etc. The model was validated and calibrated using a sample of journeys to work from agglomerations surrounding the city of Maribor.